An effector of the Irish potato famine pathogen antagonizes a host autophagy cargo receptor - Dagdas,YF; Belhaj,K; Maqbool,A; Chaparro-Garcia,A; Pandey,P; Petre,B; Tabassum,N; Cruz-Mireles,N; Hughes,RK; Sklenar,J; Win,J; Menke,F; et al. (eLife, 2016)
Plants use autophagy to safeguard against infectious diseases. However, how plant pathogens interfere with autophagy-related processes is unknown. Here, we show that PexRD54, an effector from the Irish potato famine pathogen Phytophthora infestans, binds host autophagy protein ATG8CL to stimulate autophagosome formation. PexRD54 depletes the autophagy cargo receptor Joka2 out of ATG8CL complexes and interferes with Joka2's positive effect on pathogen defense. Thus, a plant pathogen effector has evolved to antagonize a host autophagy cargo receptor to counteract host defenses.